Deportations in Western Ukraine: punishment for disloyalty (1939–1941) - Lysenko , Aleksandr (Genocidas ir rezistencija, 2008)
Forced migration was also used by the Bolshevik regime in the 1920s and 1930s as an instrument of repressive policy. The first victims of the deportations from Ukraine to distant parts of the country were the peasants who were deprived of their property. They constituted the first mass contingent needed to implement the state’s policy of special colonisation. It was the state that sought to cultivate the uninhabited and sparsely populated areas of the country through forced relocations. This policy was designed to solve two problems at once: to exclude the ‘unreliable’ population from the European part of the country, and to exploit cheap labour – the labour of many people whose rights were restricted.